2023
DOI: 10.3390/diagnostics13122091
|View full text |Cite
|
Sign up to set email alerts
|

Lung Ultrasonography Is an Acceptable Imaging Modality to Diagnose COVID-19 and Effectively Correlates with HRCT Chest—A Prospective Study

Abstract: It has been validated beyond doubt that High-Resolution Computed Tomography (HRCT) chest and to some extent chest radiographs have a role in corona virus disease-19 (COVID-19). Much less is known about the role of lung ultrasonography (LUS) in COVID-19. In this paper, our main purpose was to gauge the relationship between LUS and chest HRCT in reverse transcriptase polymerase chain reaction (RT–PCR) documented cases of COVID-19, as well as in those with high suspicion of COVID-19 with negative RT–PCR. It was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…A recent prospective study of 152 patients showed a significant relationship between high-resolution chest computed tomography (HRCT) and LUS. Importantly, no positive findings on computed tomography were missed on lung ultrasound [ 10 ]. Additionally, when different scenarios are examined, the severity of LUS findings appears to be associated with clinical outcomes [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent prospective study of 152 patients showed a significant relationship between high-resolution chest computed tomography (HRCT) and LUS. Importantly, no positive findings on computed tomography were missed on lung ultrasound [ 10 ]. Additionally, when different scenarios are examined, the severity of LUS findings appears to be associated with clinical outcomes [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…An endoscopic lung imaging technique combines the advantages of whole-lung structure imaging with the ability of a morphological examination to reveal a fine subcellular structure. Modern non-invasive imaging methods such as ultrasonography, computed tomography (CT), magnetic resonance imaging (MRI), and positron emission tomography (PET) allow detailed and dynamic 3D analysis of anatomical structures in living organisms, but these methods have a limited spatial resolution, which is often not sufficient to visualize tissue and cell microstructures [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Optical coherence tomography (OCT) has considerable potential for lung microstructure analysis [20][21][22].…”
Section: Introductionmentioning
confidence: 99%